The concurrent intervention of the spouse as a requirementfor the effectiveness of the legal act according to article 315 of the peruvian Civil Code - Arias -Stella Castillo, Fernando (2012)
Brief refiection on thevarious interpretations that are being made on article 315 ofthe Peruvian Civil Code, because the position of the relative jurisprudence, related to considering the referred article as grounds for nullity of the legal act due to the lack of manifestation of will of the agent, is being questioned in terms of doctrine. The text approaches us to the notion that the lack of participation of the spouse in acts of disposi tion of the join t property is notan infringemen t of the hard cor e of the Legal Act because of a lack of manifestation of will; instead of this, properly speaking it would grounds for inefficiency.